2017
DOI: 10.1371/journal.pone.0188848
|View full text |Cite
|
Sign up to set email alerts
|

Self-microemulsifying drug delivery system and nanoemulsion for enhancing aqueous miscibility of Alpinia galanga oil

Abstract: Alpinia galanga oil (AGO) possesses various activities but low aqueous solubility limits its application particularly in aquatic animals. AGO has powerful activity on fish anesthesia. Ethanol used for enhancing water miscible of AGO always shows severe side effects on fish. The present study explores the development of self-microemulsifying drug delivery systems (SMEDDS) and nanoemulsions (NE) to deliver AGO for fish anesthesia with less or no alcohol. Pseudoternary phase diagrams were constructed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
1
9
0
2
Order By: Relevance
“…Moreover, the different types of surfactant and co-surfactants also affected the ME region in the phase diagrams as well as the ratio of Smix [ 29 , 34 ]. Our previous work found that Tween 80 and ethanol at a weight ratio of 2:1 was the best ratio and was an appropriate Smix for AGO in providing the largest monophasic area or ME area in the phase diagrams [ 35 ]. Therefore, Tween 80 and ethanol at this ratio were used as Smix in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the different types of surfactant and co-surfactants also affected the ME region in the phase diagrams as well as the ratio of Smix [ 29 , 34 ]. Our previous work found that Tween 80 and ethanol at a weight ratio of 2:1 was the best ratio and was an appropriate Smix for AGO in providing the largest monophasic area or ME area in the phase diagrams [ 35 ]. Therefore, Tween 80 and ethanol at this ratio were used as Smix in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Tween 80, and 70% w/w water was prepared according to a method previously described as it was reported that NE-AGO formulated by this method was chemically stable when stored at various temperatures (4°C, 20°C, and 40°C) for several weeks (0, 4, 8, 12 weeks) 7 . Briefly, the aqueous phase composed of Tween 80 and water was mixed using a vortex mixer for 5 min.…”
Section: Preparation and Characterization Of Ne-ago Ne-ago Composed Of 20%w/w Ago 10%w/wmentioning
confidence: 99%
“…A. galanga is well-known in Asian folk medicine and has been used for centuries as a food additive, an antimicrobial agent, a local anesthetic, an analgesic, and an antipruritic [3][4][5][6] . A. galanga oil (AGO) is rich in 1,8-cineole and 4-allylphenyl acetate 7 . AGO was recently shown to act as an anesthetic in fish 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Lipid-based drug delivery systems (LbDDS) can improve the apparent solubility, miscibility, and oral bioavailability of many poorly water-soluble drugs [ 11 , 12 ]. These systems are generally composed of oils, surfactants, and co-surfactants.…”
Section: Introductionmentioning
confidence: 99%